Praktik dan Fungsi Sosial Ritual Jamu Laut dalam Relasi Tekong Melayu dan Pemilik Kapal Tionghoa di Tanjungbalai - Rizky Azman Munthe; Irwansyah I; Aulia Kamal (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The jamu laut ritual is a maritime tradition that continues to be practiced by coastal communities in Tanjungbalai City. This ritual is performed not only by Malay fishermen but also involves ethnic Chinese boat owners within cross-ethnic working relationships. This study aims to analyze the practice of the jamu laut ritual and its social functions in establishing and maintaining labor relations between Malay tekong (boat captains) and ethnic Chinese boat owners. The research employs a qualitative method with a descriptive-analytical approach. Data were collected through in-depth interviews, participant observation, and documentation. The primary informants included boat owners, tekong, fishermen, and members of the surrounding community. Data were analyzed using the sociology of religion perspective, particularly Emile Durkheim's theoretical framework. The findings reveal that the jamu laut ritual functions not only as an expression of belief in safety and protection at sea but also as a mechanism for legitimizing labor relations, managing occupational risks and work-related anxiety, providing a neutral space for cross-ethnic interaction, and strengthening social capital and mutual trust within fishermen's working relationships. However, the ritual's social functions are conditional and have limitations when confronted with economic interests and the demands of fishing productivity. This study highlights that local religious rituals play a significant social role in maintaining labor stability and fostering cross-ethnic tolerance within coastal communities.